PERAN SEKOLAH INDONESIA JOHOR BAHRU DALAM MEMBERIKAN LAYANAN PENDIDIKAN BAGI ANAK PEKERJA MIGRAN INDONESIA - Ul Haq, Nurul Jannah; Takwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Education is a fundamental right of every child, including the children of Indonesian migrant workers (PMI) in Malaysia. However, various challenges such as immigration status, financial constraints, and Malaysian education policies that limit access for non-citizen children pose significant obstacles to their access to formal education. This study aims to analyze the role of Sekolah Indonesia Johor Bahru (SIJB) in providing educational services for PMI children in Malaysia. This research employs a qualitative method with a descriptive approach to illustrate the educational phenomenon of PMI children in Johor Bahru. Data were collected through literature studies, interviews, and direct observations of SIJB activities. The findings indicate that SIJB serves as an alternative educational institution that provides access for PMI children who are unable to attend Malaysian public schools. SIJB offers an education program based on the Indonesian curriculum with various adjustments to meet the needs of migrant children. Additionally, SIJB collaborates with the Consulate General of the Republic of Indonesia (KJRI) in Johor Bahru to assist students in obtaining legal documents, enabling them to pursue higher education. The existence of SIJB demonstrates the commitment of the Indonesian government, through KJRI Johor Bahru, to ensuring the right to education for PMI children while also serving as a form of educational diplomacy in Malaysia. With various programs and support provided, SIJB plays a crucial role in bridging the educational access gap for PMI children. Keywords: Education, Indonesian School of Johor Bahru, Indonesian Migrant Workers, Educational Access